Synthesis,characterization and performance of triethanolamine-based thin film composite nanofiltration membrane - Nurul Ain, Jalanni (2015)
Humic acid (HA) is one of the common NOM which contribute a major problem in treatment of surface water including (i) negative effect on water quality by colour, taste and odour problems, (ii) increased coagulant and disinfectant dose requirement (iii) promoted biological growth in distribution system and (iv) increased levels of complexes heavy metals and adsorbed organic pollutants. Thus, more efficient method for the humic acid removal has emerged. Among the membrane processes, nanofiltration (NF) has been increasingly used for wastewater and water treatments including natural organic matters (NOM). Nine membranes were prepared through interfacial polymerization of aqueous solution, triethanolamine (TEOA) and organic solution, trimesoyl chloride (TMC) on a polyethersulfone (PES) support film. The composite membranes were prepared under different TEOA monomer concentration (4, 6, 8 % w/v) and reaction times (15, 25, and 35 min). These membranes were characterized in terms of chemical properties (functional group and hydrophilicity) and morphological structures to verify polyester membrane formed on the top surface of PES (interfacial polymerization process). On top of that, membrane performance was also investigated in term of pure water permeability, rejection of charged (sodium chloride (NaCl) and sodium sulphate (Na2SO4)) and uncharged solutes (vitamin B12). All nine polyester membranes showed NF characteristics which in between 12.98 L m2h-1bar-1until 1.25 L m2h-1bar-1. Analysis done by attenuated total reflectance fourier transform infrared spectroscopy (ATR-FTIR) on top surface and field emission scanning electron microscopy (FESEM) on top and cross sectional membrane indicate a new polyester layer formed on the PES membrane support. Highest TEOA monomer concentration (8% w/v TEOA) and reaction time membrane (35 min) resulted as less hydrophobicity membrane when achieved the lowest contact angle measurement (θ = 34.0 ± 0.35) compared to unmodified membrane (θ = 62.6 ± 0.33). Using uncharged (Vitamin B12)/charged solute (NaCl) data, the changes in the morphological and electrical properties of the synthesized NF membranes were deduced by employing the combination of irreversible thermodynamic model, Steric-Hindrance Pore (SHP) model and Teorell–Meyer–Sievers (TMS) model. In NF membrane characterization, three important parameters have been identified as an effective pore radius (rp), the ratio of effective thickness over porosity (Δx/Ak) and an effective charged density (Xd). In this study, it was observed that the variation of reaction times and TEOA monomer concentrations affect the properties of the membrane produced and affect water permeabilities and solute rejection as well. The salt rejection order of the membrane changed from 0.001 M Na2SO4> 0.1M Na2SO4> 0.001M NaCl> 0.1M NaCl. Moreover, pH of humic acid solution plays an important role in flux reduction and fouling. HA filtration analysis was preferably chosen at pH 7 (4% 35 min) and pH 3 (4% 15 min) respectively It observes that all nine membranes able to removes humic acid with an efficiency of approximately 98% and were capable of reducing initial concentrations of 15 mg/L at the TEOA monomer concentration (6% w/v TEOA) and reaction time (35 min).